ANALISIS PEMIKIRAN CHARLES BALLY DAN AMIN AL-KHULY DALAM STILISTIKA MODERN - Achmad Amin Zuhdi; Apip Ansurulloh Sidiq; Rizzaldy Satria Wiwaha (STKIP Subang, 2026)
ABSTRACT This article examines the ideas of two prominent scholars in stylistics from different intellectual traditions: Charles Bally, representing the European linguistic tradition, and Amin Al-Khuly, representing the tradition of Arabic literary criticism. Using a comparative-analytical approach, this study explores the core concepts developed by each scholar, including Bally’s concept of affective value and Al-Khuly’s principle of manhaj al-adabi (literary method). The findings indicate that despite their different intellectual backgrounds and contexts, both scholars share significant epistemological commonalities, particularly in their emphasis on the relationship between language, expression, and culture. This study contributes to the development of comparative stylistics in the Indonesian academic context while fostering scholarly dialogue between Western and Arabic stylistic traditions in contemporary language and literary studies. Keywords: stylistics, Charles Bally, Amin Al-Khuly, affective value, manhaj al-adabi, linguistics ABSTRAK Artikel ini mengkaji pemikiran dua tokoh stilistika yang berasal dari tradisi intelektual berbeda, yakni Charles Bally dari tradisi linguistik Eropa dan Amin Al-Khuly dari tradisi kritik sastra Arab. Melalui pendekatan komparatif-analitis, kajian ini menelusuri konsep-konsep inti yang dibangun oleh masing-masing tokoh, termasuk gagasan affective value dalam stilistika Bally dan prinsip manhaj al-adabi (metode sastra) dalam pemikiran Al-Khuly. Hasil kajian menunjukkan bahwa meskipun keduanya bertolak dari tradisi dan konteks yang berbeda, terdapat titik-titik pertemuan epistemologis yang signifikan, terutama dalam hal penekanan terhadap hubungan antara bahasa, ekspresi, dan kebudayaan. Kajian ini berkontribusi pada pengembangan stilistika komparatif di lingkungan akademik Indonesia, sekaligus membuka ruang dialog antara tradisi stilistika Barat dan Arab dalam konteks kajian bahasa dan sastra kontemporer. Kata Kunci: stilistika, Charles Bally, Amin Al-Khuly, affective value, manhaj al-adabi, linguistik